(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the complexities of studying students with deviant behavior, various approaches to correcting adolescents, and provides practical recommendations and advice for educators and psychologists. The focus is on applying psychological goals and interventions to promote positive development.